Energy Flow Boundary Element Method for Vibration Analysis of One and Two Dimension Structures - Ho-Won Lee; Suk-Yoon Hong; Do-Hyun Park; Hyun-Wung Kwon (Shock and Vibration)
In this paper, Energy Flow Boundary Element Method (EFBEM) was developed to predict the vibration behavior of one- and two-dimensional structures in the medium-to-high frequency ranges. Free Space Green functions used in the method were obtained from EFA energy equations. Direct and indirect EFBEMs were formulated for both one- and two-dimensional cases, and numerically applied to predict the energy density and intensity distributions of simple Euler-Bernoulli beams, single rectangular thin plates, and L-shaped thin plates vibrating in the medium-to-high frequency ranges. The results from these methods were compared with the EFA solutions to verify the EFBEM.